Implementation of the Class 6 Teaching Campus Program to Improve Students' Literacy and Numeracy Abilities at SMPN 2 Lenek - Dewi, Bq. Intan Patmala (Polyhedron International Journal in Mathematics Education, 2023)
This service is motivated by a Ministry of Education and Culture, Research and Technology program, namely Independent Learning Campus (MBKM) through Teaching Campus activities. The Teaching Campus was introduced and implemented in 2020; now, it has reached 6. The Teaching Campus program aims to open up space for students from various tertiary institutions to assist the learning process from various schools in Indonesia, which are in the 3T areas (Disadvantaged, Frontier, and Outermost). One of the schools where the 6 Teaching Campus program is implemented is SMPN 2 Lenek. The program's scope that students have implemented during assignments is to help improve students' abilities in literacy and numeracy, assist teachers in improving the quality of learning through technological and administrative adaptation assistance, and develop students' character. The results obtained while implementing the 6 Teaching Campus activity program positively impacted students' numeracy literacy skills, character development, and teachers' abilities to adapt to technology. Students become more fluent in reading and understanding the contents of the books they read, they get used to being disciplined and responsible for the tasks given, and teachers use technology to create learning media in the learning process.